Intentionality as a category of social interaction (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the phenomenon of intention and intentionality, as a prerequisite for the formation of social relationships and social interaction factor. The author makes an attempt to understand the problem of interaction between language and power from the perspective of social ontology, as the main factors in the formation of the social world. In addition, the article touched on collective intentionality, using of status functions and role of constitutive rules in the constructing and functioning of institutional reality. The problem of intentionality is popular in modern philosophy as the question of orientation, orientation of human consciousness in the broad anthropological sense. It involves the active participation of the subject, defining the basis and parameters of the intentions.Key words: social reality, intentionality, collective intentionality, language, power, intention, the status functions, constitutive rules.